Analysis and design of fractional-order digital control systems - Machado, J. A. Tenreiro (2016)
The paper presents a novel method for the design of fractional-order digital controllers. The theory oof fractional derivatives and integrals (FDI's) is still in a research stage but the recent progress in the areas of chaos and fractal reveals promising aspects for future developments. In the field of automatic control systems some preliminary work has been carried out but the results are restricted to the frequency domain. The algorithms z-transform analysis and digital implementation. For a prototype mechanical system the control algorithm based on the new concepts reveals that classical P, I and D actions are, in fact, special cases of a more brad paradigm. In this line of thought, this study represents a first stage towards the development of motion controol systems based on the theory of FDI's